IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS GOOGLE CLASSROOM PADA MATAPELAJARAN PENDIDIKAN AGAMAISLAM DI SMP WAHID HASYIM MALANG - M Muslih; Rosichin Mansur; Indhra Mustofha (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Learninggmediaais one of the importantttools in the learninggprocess,becauseewithhlearning mediaastudentsswill more easily understand what isexplained by the master in learninggexpositions. Stage Google Classroom is amediummthat can be used as a learning medium, because it uses applicationssthathelp the learning processsand provideea pleasant effect forsstudents. The focussof thisresearchhdiscussespplanning,iimplementation, anddevaluation. To achieve this goal,this study uses a phenomenological-based qualitative approach with instruments ofobservation, interviews, and documentation. Research founddthe result of this studyincludeeimplementation planninggaccording to recommendationssfrom thegovernmentt. In theeimplementationnof IslamiccReligious Educationnresearch, itincludes time indicators, applications used, slightly openmmaterials, learning andevaluationnmethods. Thee supportinggand inhibiting factors of this research areadequate facilities and infrastructure. Assfor the supporting and inhibitinggfactorsoffthissresearch, some studentssare constraineddby problematic web networks